1995
DOI: 10.1111/j.1439-0523.1995.tb01256.x
|View full text |Cite
|
Sign up to set email alerts
|

An agronomic and seed‐quality evaluation of noug (Guizotia abyssinica Cass.) germplasm in Ethiopia

Abstract: Noug {Guizotia abyssinica Cass.), a member ofthe Compositae family, is grown as an oilseed crop in Ethiopia. The crop grows best on poorly drained, heavy clay soils. This study investigates the genetic variability of agronomic and seed quality characteristics of 241 noug germplasm collections from different parts of Ethiopia evaluated in a field test at Ghinchi, near Addis Ababa, Ethiopia, in 1992, The maturity of the noug accessions ranged from 132 to 168 days. Seed oil contents ranged from 39.8 to 46.9% with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 1 publication
0
17
0
Order By: Relevance
“…Contrary to Gojam, the mean within population genetic diversity for Welo was found to be the highest and significantly higher than most of the means of other regions. Thus, this study provides further illustration of the reported agromorphological variation (Alemaw and Teklewold 1995;Genet and Belete 2000) and variation in oil content (Dutta et al 1994;Dagne 1994;Alemaw and Teklewold 1995) for Ethiopian niger. Genet and Belete (2000) estimated the diversity of Ethiopian niger using phenological and morphological characters and indicated that regionally the highest Shannon diversity index was recorded for Gojam.…”
Section: Genetic Diversitymentioning
confidence: 84%
See 2 more Smart Citations
“…Contrary to Gojam, the mean within population genetic diversity for Welo was found to be the highest and significantly higher than most of the means of other regions. Thus, this study provides further illustration of the reported agromorphological variation (Alemaw and Teklewold 1995;Genet and Belete 2000) and variation in oil content (Dutta et al 1994;Dagne 1994;Alemaw and Teklewold 1995) for Ethiopian niger. Genet and Belete (2000) estimated the diversity of Ethiopian niger using phenological and morphological characters and indicated that regionally the highest Shannon diversity index was recorded for Gojam.…”
Section: Genetic Diversitymentioning
confidence: 84%
“…The Press cake left after the oil has been extracted is found to be an excellent animal feed as it contains about 33% protein (Kandel and Porter 2002). The oil content of the niger seed vary considerably and the most abundant fatty acid is linoleic acid as reported by different authors (Dutta et al 1994;Alemaw and Teklewold 1995;Dagne and Jonsson 1997;Ramadan and Mörsel 2002).…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…It is a dicotyledonous herb, moderately to well branched, and grows up to 2 m in height (Getinet and Teklewold, 1995). The crop grows best on poorly drained, heavy clay soils (Alemaw and Wold, 1995;Francis and Campbell, 2003). Niger is cultivated in both temperate and tropical climates, being considered a temperate-region plant that has adapted to a semi-tropical environment.…”
Section: Introductionmentioning
confidence: 99%
“…Means followed by same letter were not significantly different from each other (p \ 0.05, ANOVA). c RIL-181 (Tesfa) grown in the field at Debre Zeit in black Vertisols Campell 1997;Brandt 1997;Alemaw and Teklewold 1995). Unlike the introduced global crops, these indigenous crops have the major advantage that they fit well into the general socio-economic and ecological context of the region (Tadele 2009;Tadele and Assefa 2012).…”
Section: Outlook and Prospectsmentioning
confidence: 99%